Weighted Estimates for Bilinear Operators. (6th February 2014) - Zhu, Hua; Liu, Heping
Abstract : We study the boundedness of weighted multilinear operators given by products of finite vectors of Calderón-Zygmund operators. We also investigate weighted estimates for bilinear operators related to Schrödinger operator.